A Flexible PV-Powered Battery-Charging Scheme for Electric Vehicles. Issue 2 (4th March 2017) - Sharaf, Adel M.; Şahin, Mustafa E.
ABSTRACT: This paper presents a new design for a low-impact, fully controlled, and flexible self-adjusting DC side pulse-width modulation (PWM)-hybrid modulated filter compensation (HMFC) scheme for multi photovoltaic-arrays utilized for vehicle-to-grid battery-charging electric vehicle schemes. The flexible HMFC scheme developed by the first author as a member of dynamic hybrid capacitor compensation and filtering scheme is robust and effective as it ensures maximum energy utilization and low inrush current transients. In addition, it provides transient voltage damping for a stabilized common DC interface bus to the battery charger. The new flexible controller uses a regulated multi-loop error-driven, error-scaled, and de-coupled hybrid mode charging controller for the PWM switching scheme along with two MOSFET/IGBT (Metal Oxide Semiconductor Field Effect Transistor/Insulated Gate Bipolar Transistor) complementary switches based on ratings and are cascaded for proper voltage and current photovoltaic (PV) arrays utilized. The dynamic error-driven controller ensures reduction in inrush current and transient voltage conditions as well as compensation for cloudy and shadowy conditions by equalizing the maximum power utilization of the two PV arrays. This will ensure efficient PV solar-system energy utilization as well as fully de-coupled source-load operation for the new proposed multi modal Li-ion battery-charging controller. The multi-regulator error-driven proportional integrated derivative controllers with newly added acceleration and fast response auxiliary loops ensure efficient fast charging as well as common DC-bus stabilization under load excursions, temporary faults, and battery hybrid voltage-current-power (V-I-P) charging modes. The hybrid switched/modulated capacitive-filter compensator ensures limited current excursions for transient DC voltage conditions.